A new shrimp species of the genus Leptomenaeus Bruce, 2007 (Crustacea: Decapoda: Pontoniinae) from Vietnam - Ďuriš, Zdenek; Horká, Ivona (Zootaxa, 2008)
A new species of pontoniine shrimp, Leptomenaeus nhatrangensis sp. nov., is described and illustrated. This new species is the second representative of the genus. It is distinguishable from L. dolichosternum (Okuno and Mitsuhashi 2003) by the straight dorsal outline of the carapace and rostrum (1), by the rostrum overreaching the basal antennular peduncle (2), a subacute lower orbital angle (3), serrate cutting edges on the first pereiopod chela (4), fingers of the second pereiopod chela not markedly longer than palm (5), and the sixth abdominal segment not distinctly longer than postorbital carapace length (6). A single specimen of this new species was found in shallows of the Nhatrang Bay, southeastern Vietnam, on the lower surface of a large boulder.